Contemplative Mental Training Reduces Hair Glucocorticoid Levels in a Randomized Clinical Trial. Issue 8 (October 2021) - Puhlmann, Lara M.C.; Vrtička, Pascal; Linz, Roman; Stalder, Tobias; Kirschbaum, Clemens; Engert, Veronika; Singer, Tania
ABSTRACT: Objective: This study aimed to investigate the effect of regular contemplative mental training on endocrine and psychological indices of long-term stress. Methods: An open-label efficacy trial that comprised three distinct 3-month long modules targeting attention and interoception, socioaffective, or sociocognitive abilities through dyadic exercises and secularized meditation practices was conducted with healthy adults. Participants underwent the training for 3 or 9 months, or were assigned to a retest control cohort. Chronic stress indices were assayed at four time points: pretraining and after 3, 6, and 9 months. The main outcome measures were cortisol (HC) and cortisone (HE) concentration in hair and self-reported long-term stress. Results: Of 362 initially randomized individuals, 30 dropped out before study initiation ( n = 332; mean [SD] age = 40.7 [9.2] years; 197 women). Hair-based glucocorticoid assays were available from n = 227, and questionnaire data from n = 326. Results from three separate training cohorts (TC1–3) revealed consistent decreases in HC and HE levels over the first three (TC3) to 6 months (TC1 and TC2) of training, with no further reduction at the final 9-month mark (baseline to end of training differences, HC, TC1: t (355) = 2.59, p = .010, contrast estimate (est.) [SE] = 0.35 [0.14]; HC, TC2: t (363) = 4.06, p < .001, est. = 0.48 [0.12]; HC, TC3: t (368) = 3.18, p = .002, est. = 0.41 [0.13]; HE, TC1: t (435) = 3.23, p = .001, est. = 0.45 [0.14]; HE, TC2: t (442) = 2.60, p = .010, est. = 0.33 [0.13]; HE, TC3: t (446) = 4.18, p < .001, est. = 0.57 [0.14]). Training effects on HC increased with individual compliance (practice frequency), and effects on both HC and HE were independent of training content and unrelated to change in self-reported chronic stress. Self-reported stress, and cortisol-to-dehydroepiandrosterone ratios as an exploratory endpoint, were also reduced, albeit less consistently. Conclusions: Our results point to the reduction of long-term cortisol exposure as a mechanism through which meditation-based mental training may exert positive effects on practitioners' health. Trial Registration : ClinicalTrials.gov identifier: NCT01833104. Abstract : Supplemental digital content is available in the text.